Kecerdasan Emosional Perawat terhadap Komunikasi Interpersonal dengan Pasien - IGAA Sherlyna Prihandhani; Nina Rismawati Hakim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between nurses' emotional intelligence and interpersonal communication with patients at Siloam Hospital Bali. This research method is an observational analytic study using a cross-sectional approach. The survey results to 180 respondents using the Chi-Square correlation analysis technique obtained a p-value of 0.001 with a value of Î± = 0.05. In conclusion, there is a significant relationship between nurses' emotional intelligence and interpersonal communication with patients at Siloam Hospital Bali. The most influential variables were self-motivation, social relations, and empathy, and nurses who had high heart had 2.716 times the chance of having high interpersonal communication compared to nurses who had low heart. Keywords: Emotional Intelligence, Interpersonal Communication, Nurse